Augmented Reality Dance Teaching Module as a Strategy to Enhance Elementary School Students' Learning Interest - Inke Firdaus; Agus Budiman; Juju Masunah; Saian Badaruddin; Aimi Nabila Anizaim; Tati Narawati (Yayasan Keluarga Guru Mandiri, 2026)
The development of Augmented Reality technology offers new opportunities in education by providing visual, interactive, and exploratory learning experiences, particularly in dance learning that requires strong visual comprehension. This study aims to develop, implement, and evaluate the effectiveness of an AR-based dance-teaching module to increase elementary students’ interest in learning. Grounded in a pragmatic paradigm, the research employed a mixed-methods approach using the Design and Development method. Participants included AR experts, dance teachers, and 20 fifth-grade students from Cendekia Leadership School Bandung. Data were collected through interviews, observations, expert validation, tests, and questionnaires, while learning interest was analyzed using the SAFARI indicators: pleasure, interest, attention, and active involvement. Statistical analysis included normality testing, paired-samples t-tests, and N-Gain calculations. Results showed the module was rated “Very Feasible” by experts with a mean score of 90.97%. Field testing indicated significant improvement in student scores from a pre-test mean of 60.15 to a post-test mean of 80.45, with a significant difference (p 0.001) and a high N-Gain of 0.81. Questionnaire findings revealed students’ learning interest reached a Very High level (92.19%). Therefore, the AR-based module effectively enhances learning interest through interactive, visually engaging dance instruction for elementary learners.